ANALISIS PERAN PENGURUS KARANG TARUNA DALAM PEMBINAAN KECAKAPAN HIDUP (LIFE SKILLS) REMAJA - Fitrian Fitrian; Imran Imran; Rum Rosyid (Universitas Tanjungpura, 2020)
AbstractThe aim of this research was to know about the role of youth organization in coaching youth life skills at Desa Gunung Gajah Sejahtera Kecamatan Pemangkat. This research used qualitative research with descriptive method. The techniques of data collection were observation, interview and the study of documentation, where as the tools of data collection were the directive of observation, directive of interview, the notes and the files. This research sources were primer data and secodary data. The result of the research indicate that life skills that occur in coaching conducted by the management of youth organizations occur very well and are interrelated. Personal skill consisting of the ability to dig up information and the ability to solve problems occur very well, then social skill consisting of the ability to communicate, have a sense of empathy, and the ability to work together in the coaching also occur very well.Keywords : Role, Youth Organization, Youth Coaching